2019
DOI: 10.1111/pops.12598
|View full text |Cite
|
Sign up to set email alerts
|

Anger Mediates the Effects of Fear on Support for the Far Right—A Rejoinder

Abstract: We are grateful to John Jost for carefully engaging with our work and presenting a different interpretation of our findings on the effects of fear and anger stemming from the November 13, 2015, Paris attacks on the propensity to vote for the far right. Jost advances a model that holds that anger mediates the effect of fear on support for the far right. In this rejoinder, we respond to the issues he raises regarding our model specification, consider his alternative suggestion, and offer some conclusions about … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 29 publications
2
9
0
Order By: Relevance
“…OR ϭ 1.040, 99% CI [1.019, 1.058]). They also sent more tweets with anger-related language, OR ϭ 1.041, 99% CI [1.019, 1.065], consistent with public opinion data suggesting that rightists tend to express more anger than leftists (Jost, 2019;Vasilopoulos et al, 2019). No ideological differences were observed in the use of positive emotion (H25) or anxiety language (H18; as reported above), contrary to expectations.…”
Section: Results For Emotional Expressionsupporting
confidence: 78%
See 1 more Smart Citation
“…OR ϭ 1.040, 99% CI [1.019, 1.058]). They also sent more tweets with anger-related language, OR ϭ 1.041, 99% CI [1.019, 1.065], consistent with public opinion data suggesting that rightists tend to express more anger than leftists (Jost, 2019;Vasilopoulos et al, 2019). No ideological differences were observed in the use of positive emotion (H25) or anxiety language (H18; as reported above), contrary to expectations.…”
Section: Results For Emotional Expressionsupporting
confidence: 78%
“…Consistent with these ideas, Robinson and colleagues (2014) observed that liberals used more language related to anger than conservatives did, and conservatives used more language related to anxiety than liberals did. At the same time, public opinion research suggests that rightists may be more driven by anger (and fear), in comparison with leftists, so we considered this possibility as well (Jost, 2019;Vasilopoulos, Marcus, Valentino, & Foucault, 2019). Thus, we investigated the hypothesis proposed by Robinson et al (2014) that liberals would use more anger-related language than conservatives (H27) and (as noted above) that conservatives would use more anxiety-related language than liberals (H18).…”
Section: Emotional Expressionmentioning
confidence: 97%
“…Counterintuitively, the present data also indicated a negative relationship between anxiety and RWPP support. This pattern corresponds to an ongoing discussion concerning the role of anger and anxiety on RWPP support (Jost, 2019;Vasilopoulos, Marcus, Valentino, & Foucault, 2019a, 2019b. Contrary to the stable relationship between anger and RWPP support, the present data support different interpretations on the role of anxiety (see Supplementary Materials for additional analysis).…”
Section: Affective Consequences Of Reduced Need Satisfaction and Theisupporting
confidence: 82%
“…Further research may seek to disentangle the effect of SWB on each of these types of candidate. Research in social psychology has shown, for example, that negative emotions such as fear and anger contribute to support for right-wing, authoritarian candidates (e.g., Jost, 2019;Vasilopoulos, Marcus, Valentino, & Foucault, 2019). In general, we find the effects of low SWB to have been stronger in the primaries for Trump than for Sanders (whose populism did not incorporate an anti-immigrant strand), which provides some initial suggestive evidence for an ideological asymmetry whereby nativist right-wing populism draws in more unhappy people than left-wing, nonnativist strands of populism.…”
Section: Discussionmentioning
confidence: 99%